PEMBANGUNAN RUMAH BIBIT KAYU MANIS BERBASIS KOMODITI UNGGULAN DAERAH KABUPATEN KERINCI - Chatra, Afdhal; Yelnim , Yelnim (Batara Wisnu : Indonesian Journal of Community Services, 2023)
The purpose of this community service activity in building a nursery is to help farmers in Gunung Kerinci District obtain quality cinnamon seeds, considering that cinnamon is a regional commodity and as one of the steps to maintain the sustainability of cinnamon plants in Kabupaten Kerinci . This community service activity is a collaborative activity between the lecturers of the development economics study program and STIE Sakti Alam Kerinci students together with farmer groups in the village of Air Betung, Kabupaten Kerinci which was carried out for two months from December 2022 to mid-January 2023. The results of the wooden seedling house This sweet can be used by the farming community in Air Betung village in particular and farmers in Gunung Kerinci District in general